Barriers, facilitators, and proposals for improvement in the implementation of a collaborative care program for depression: a qualitative study of primary care physicians and nurses - Enric Aragonès; Germán López-Cortacans; Narcís Cardoner; Catarina Tomé-Pires; Daniel Porta-Casteràs; Diego Palao; the INDI·I Research Team (BMC, 2022)
Abstract Background Primary care plays a central role in the treatment of depression. Nonetheless, shortcomings in its management and suboptimal outcomes have been identified. Collaborative care models improve processes for the management of depressive disorders and associated outcomes. We developed a strategy to implement the INDI collaborative care program for the management of depression in primary health care centers across Catalonia. The aim of this qualitative study was to evaluate a trial implementation of the program to identify barriers, facilitators, and proposals for improvement. Methods One year after the implementation of the INDI program in 18 public primary health care centers we performed a qualitative study in which the opinions and experiences of 23 primary care doctors and nurses from the participating centers were explored in focus groups. We performed thematic content analysis of the focus group transcripts. Results The results were organized into three categories: facilitators, barriers, and proposals for improvement as perceived by the health care professionals involved. The most important facilitator identified was the perception that the INDI collaborative care program could be a useful tool for reorganizing processes and improving the management of depression in primary care, currently viewed as deficient. The main barriers identified were of an organizational nature: heavy workloads, lack of time, high staff turnover and shortages, and competing demands. Additional obstacles were inertia and resistance to change among health care professionals. Proposals for improvement included institutional buy-in to guarantee enduring support and the organizational changes needed for successful implementation. Conclusions The INDI program is perceived as a useful, viable program for improving the management of depression in primary care. Uptake by primary care centers and health care professionals, however, was poor. The identification and analysis of barriers and facilitators will help refine the strategy to achieve successful, widespread implementation. Trial registration ClinicalTrials.gov identifier: NCT03285659 ; Registered 18th September, 2017.